RESPON PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (BRASSICA RAPA L.) TERHADAP KONSENTRASI BIOBOOST CAIR DAN DOSIS NPK ENTEC - IRAWATY ROSALYNE; ROSMADELINA PURBA; NOYA PRAMESARI (LP2MTBM MAKARIOZ, 2023)
The research was conducted in December 2021 in Sait Buntu Village, Sidamanik District, Simalungun Regency. This study aims to determine the growth and yield response of pakcoy plants due to a combination of liquid bioboost concentration and entec NPK doses on the growth and production of pakcoy plants (Brassica rapa L.). Objectives This research was conducted using a Factorial Randomized Group Design (RAK), consisting of two factors, namely: The first factor is the application of bioboost fertilizer (B) which consists of 4 levels, namely B0 = Without bioboost treatment, B1 = 160 cc / 2 L of water per plot, B2 = 180 cc / 2 L of water per plot, B3 = 200 cc / 2 L of water per plot and the second factor is the addition of Entecpertanaman fertilizer dose (N) which consists of 3 levels, namely N1 = 25 g / plot, N2 = 50 g / plot, N3 = 75 g / plot. The parameters observed were plant height (cm), number of leaves (strands), net weight per plant (g) and net weight per plot (kg). The results of the study explained that there was a real response to the growth and production of pakcoy due to the application of bioboost concentrations on plant height at the age of 14 and 28 HST, the number of leaves at the age of 14 and 28 HST, net weight per plant and net weight per plot. There was a significant response in plant height at 28 HST, number of leaves at 28 HST, net weight per plant and net weight per plot to the dose of Entec NPK fertilizer but there was no significant response in plant height at 14 HST and number of leaves at 14 HST. The interaction response of bioboost biofertilizer and NPK Entec fertilizer had a real response to plant height at 28 HST and net weight per plant but there was no real response to plant height at 14 HST, the largest number of leaves at 14 and 28 HST and net weight per plot.